STUDI PENGARUH DAYA TARIK J-ROCKS DAN BRAND ATTITUDE TERHADAP MINAT BELI IM3 - Subagio, Hendrawan Oktavianto (Master of Management Diponegoro University, 2010)
Purpose – The purpose of this paper is to examine the purchase intention of IM3.Design/methodology/approach – This paper using multiple regression analysis to examinethe purchase intention of IM3.Findings – This paper finding that purchase intention of IM3 affected by J-Rocks Attractivenessand Brand Attitude.Research Limitations – It is found that the value of adjusted R square is only 0,308. It is meanthat J-Rocks Attractiveness and Brand Attitude can explain only 30,8% of purchase intentention of IM3